Investigation of calculation models of the engine installation effects on aircraft noise levels - Запорожець, О. І.; Токарев, В. І.; Голембієвський, Г. Г. (Proceedings of National Aviation University (archive), 2021)
The engine installation effects on aircraft noise levels are investigated in the article - shielding, reflecting and refraction of the sound waves on the elements of the aircraft frame and ensmes.